2008
DOI: 10.1007/bf03179344
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the different uncertainty models in dose expected volume histogram computation

Abstract: Dose expected volume histograms are a useful alternative to dose volume histograms in order to take into account computation uncertainty when prescribing, planning and reporting external beam radiation therapy. Due to the type B nature of computation uncertainties, a rectangular probability distribution was assumed in its definition. In the present work, the changes of dose expected volume histograms when using other recommended point dose uncertainty models are investigated. Results show that the choice of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…We have not encountered any technique available in the literature that can be as comprehensive as Polynomial Chaos Expansion can. Throughout Section 3.3 we have shown that PCE can practically yield all previously introduced sensitivity and uncertainty metrics, such as expected DVHs and the standard deviation of the DVH [10], DVH bandwidths for arbitrary confidence levels [28,36,29,25], dose standard deviation distribution and Standard Deviation Volume Histograms [5,8], PDFs of point doses and dose interval probabilities [26,10], Dose Population Histograms [27,37], error volume histograms [21], etc. What makes PCE unique is the speed and accuracy with which it can provide all these, and in particular its ability to enable the derivation of the spatial distribution of the probability of under-and overdosage, exact Dose-Population Histograms and Dose-Volume Histogram Distributions, which give a far more comprehensive description of dose uncertainties than previously presented methods.…”
Section: Drawbacks and Limitationsmentioning
confidence: 99%
“…We have not encountered any technique available in the literature that can be as comprehensive as Polynomial Chaos Expansion can. Throughout Section 3.3 we have shown that PCE can practically yield all previously introduced sensitivity and uncertainty metrics, such as expected DVHs and the standard deviation of the DVH [10], DVH bandwidths for arbitrary confidence levels [28,36,29,25], dose standard deviation distribution and Standard Deviation Volume Histograms [5,8], PDFs of point doses and dose interval probabilities [26,10], Dose Population Histograms [27,37], error volume histograms [21], etc. What makes PCE unique is the speed and accuracy with which it can provide all these, and in particular its ability to enable the derivation of the spatial distribution of the probability of under-and overdosage, exact Dose-Population Histograms and Dose-Volume Histogram Distributions, which give a far more comprehensive description of dose uncertainties than previously presented methods.…”
Section: Drawbacks and Limitationsmentioning
confidence: 99%
“…Nevertheless, assuming a beta distribution (or even a normal distribution), which is parameterized by mean and standard deviation for the DVH-point, could facilitate uncertainty propagation through models that build on DVHs itself, for example, in deriving biologically effective dose, 36 or refining the statistical models for optimization purposes. 19 In comparison to the previous works, [25][26][27] our methodology directly reproduced their model for the expectation value of DVHpoints. 25 Our approach using integration directly generalizes to higher moments like covariance, while their model only yielded upper bounds on the variance because correlations between voxels were not explicitly included.…”
Section: Discussionmentioning
confidence: 84%
“…The result proved to be applicable with different families of assumed probability distributions (i.e., Gaussian, triangular and rectangular/uniform) 25,26 . However, due to the simplified uncertainty model using constant relative standard deviation and no correlation between voxels, an exact computation of higher moments of a DVH‐point's probability distribution was not attempted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations